Serum folate concentrations at diagnosis are associated with hepatocellular carcinoma survival in the Guangdong Liver Cancer Cohort study. Issue 12 (17th June 2019) - Fang, Ai-Ping; Liu, Zhao-Yan; Liao, Gong-Cheng; Chen, Pei-Yan; Wang, Xiao-Yan; Zhang, Dao-Ming; Luo, Yun; Long, Jing-An; Zhong, Rong-Huan; Zhou, Zhong-Guo; Xu, Yan-Jun; Xu, Xiao-Jun; et al.
Abstract: Existing data on folate status and hepatocellular carcinoma (HCC) prognosis are scarce. We prospectively examined whether serum folate concentrations at diagnosis were associated with liver cancer-specific survival (LCSS) and overall survival (OS) among 982 patients with newly diagnosed, previously untreated HCC, who were enrolled in the Guangdong Liver Cancer Cohort (GLCC) study between September 2013 and February 2017. Serum folate concentrations were measured using chemiluminescent microparticle immunoassay. Cox proportional hazards models were performed to estimate hazard ratios (HR) and 95 % CI by sex-specific quartile of serum folate. Compared with patients in the third quartile of serum folate, patients in the lowest quartile had significantly inferior LCSS (HR = 1·48; 95 % CI 1·05, 2·09) and OS (HR = 1·43; 95 % CI 1·03, 1·99) after adjustment for non-clinical and clinical prognostic factors. The associations were not significantly modified by sex, age at diagnosis, alcohol drinking status and Barcelona Clinic Liver Cancer (BCLC) stage. However, there were statistically significant interactions on both multiplicative and additive scale between serum folate and C-reactive protein (CRP) levels or smoking status and the associations of lower serum folate with worse LCSS and OS were only evident among patients with CRP > 3·0 mg/l or current smokers. An inverse association with LCSS were also observed among patients with liver damage score ≥3. These results suggest that lower serum folate concentrations at diagnosis are independently associated with worse HCC survival, most prominently among patients with systemic inflammation and current smokers. A future trial of folate supplementation seems to be promising in HCC patients with lower folate status.